EP1247 Early-stage cervical cancer outcomes after open, minimally invasive and vaginal surgery. Single centre experience. (1st November 2019) - Fernandez-Gonzalez, S; Calvo, I; Barahona, M; Marti, L; Ponce, J
Abstract : Introduction/Background: The management of surgical stages in cervical cancer need to be redesign based on the recent literature. However, it is not less important to know about the own experience in that field in order to reconsider further changes in daily practice. We aimed to study our outcomes in women affected by early-stage cervical cancer. Methodology: This retrospective study analyzed data for all patients with early stage (IA1, IA2, IB1) cervical cancer treated by surgery between July 2000 and April 2017 at our institution. Clinical and pathological features, recurrences, disease free-survival (DFS) and disease specific survival rates were compared between patients who received Open Surgery (laparotomy), Minimally Invasive Surgery (MIS: laparoscopy or robotic) and Vaginal Surgery (Schauta assisted by laparoscopy for lymphadenectomy). Results: A total of 107 patients were included, of whom 24 (22.4%), 65 (60.7%) and 18 (16.8%) received open, MIS or vaginal surgery respectively. The three groups were similar with respect to age, histologic subtype, FIGO stage and ECOG. Higher rates of lymphovascular invasion and tumor grade 3 were observed in vaginal and open group respectively, and lower rates of none adjuvant treatment in open surgery were observed (table 1). After a median follow-up of 99, 50 and 117 months, the DFS was 82.6%, 93.8% and 86.7% in Open, MIS and Vaginal respectively and Disease specific survival rate was 100%, 98.4% and 93.8% respectively (table 2). Conclusion: In our experience, minimally invasive radical hysterectomy was associated with higher rates of DFS and similar disease specific survival rate than Open and Vaginal radical hysterectomy among women with early-stage cervical cancer. Disclosure: Nothing to disclose